Contemporary Art in Context - Lyon, Christopher; Castleman, Riva (New York : The museum of Modern Art, 1990)
Acconci, Vito ; Aycock, Alice ; Baldessari, John ; Bickerton, Ashley ; Burton, Scott ; Cézanne, Paul ; Conwill, Houston ; Dickson, Jane ; Duchamp, Marcel ; Grosz, George ; Holzer, Jenny ; Judd, Donald ; Komar & Melamid ; Kosuth, Joseph ; Kruger, Barbara ; Le Corbusier ; Monet, Claude ; Murray, Elizabeth ; Oppenheim, Meret ; Ringgold, Faith ; Rollins, Tim ; Salle, David ; Still, Clyfford ; Tansey, Mark ; Torres, Francesc ; Wines, James
Contemporary Art in Context, The museum of Modern Art, New York, Contemporary Art in Context : Recent Acquisitions, February 29 - March 6, 1988 ; Contemporary Art in Context : Points and Views, February 29, 1988 ; etc.
boek